A walk with Jane Austen : a journey into Adventure, Love and Faith - Smith, Lori, 1971- (WaterBook Press, 2009)
Step into a Life of Grace At thirty-three, dealing with a difficult job and a creeping depression, Lori Smith embarked on a life-changing journey following the life and lore of Jane Austen through England. With humor and spirit, Lori leads readers through landscapes Jane knew and loved-from Bath and Lyme, to London and the Hampshire countryside-and through emotional landscapes in which grace and hope take the place of stagnation and despair. Along the way, Lori explores the small things, both meanness and goodness in relationships, to discover what Austen herself knew: the worth of an ordinary life.